2010
DOI: 10.2176/nmc.50.839
|View full text |Cite
|
Sign up to set email alerts
|

Application of Focal Cerebral Cooling for the Treatment of Intractable Epilepsy

Abstract: Epilepsy is usually treated with medication, but adequate seizure control is still not achieved in over 30% of epilepsy patients, even with the best available agents. Surgical treatment is also performed for such patients, but is not always successful. Focal cooling of the brain using a thermoelectric device has recently been evaluated as an alternative to epilepsy surgery. Brain cooling was first proposed approximately 50 years ago as an effective method for suppressing epileptic discharges (EDs). Recent stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 37 publications
(39 reference statements)
0
24
0
Order By: Relevance
“…It could also interact directly with the patient via a personalized electronic device, and might protect and relief anxiety, especially in the 10%-65% of the pharmacoresistant population that does not experience an epileptic aura. [29][30][31][32] Our proposed seizure type prediction algorithm, albeit being dependent on the performance of the detection algorithm, could serve to stage the degree of warning and intervention [33][34][35] depending on the risk of ictal discharges becoming symptomatic and evolving to a bilateral tonic-clonic clinical manifestation. Stepwise therapeutic increments adapted to seizures' biorhythms and acute drug administration are logical and much desired approaches in the field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could also interact directly with the patient via a personalized electronic device, and might protect and relief anxiety, especially in the 10%-65% of the pharmacoresistant population that does not experience an epileptic aura. [29][30][31][32] Our proposed seizure type prediction algorithm, albeit being dependent on the performance of the detection algorithm, could serve to stage the degree of warning and intervention [33][34][35] depending on the risk of ictal discharges becoming symptomatic and evolving to a bilateral tonic-clonic clinical manifestation. Stepwise therapeutic increments adapted to seizures' biorhythms and acute drug administration are logical and much desired approaches in the field.…”
Section: Discussionmentioning
confidence: 99%
“…28 Seizure prediction algorithms offer an alternative, in theory, but so far systematic reviews have demonstrated limited performance and replicability. [29][30][31][32] Our proposed seizure type prediction algorithm, albeit being dependent on the performance of the detection algorithm, could serve to stage the degree of warning and intervention [33][34][35] depending on the risk of ictal discharges becoming symptomatic and evolving to a bilateral tonic-clonic clinical manifestation.…”
mentioning
confidence: 99%
“…The ability to define and characterize a network of brain-tissue that is involved in seizure generation or is required to modulate the process of seizure-generation is of increasing interest to clinicians, researchers, and the medical device industry. The presented methods may help guide the surgical implantation of electrodes for electrical pacemakers (Fisher et al, 2010; Fountas et al, 2005) or thermoelectric probes for focal cooling (Fujii et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…The potential for using similar devices for delivery of other types of therapy (e.g. drugs, focal cooling) also exists [3739]. …”
Section: Embeddingmentioning
confidence: 99%